Answer:
2 sets I think
Step-by-step explanation:
what are the answer choices
Answer:
First break up 72 into
36 x 2 x -1
Then take the square root of 36
6 square root 2 x -1
Finally make square root -1 = i
6i square root 2 is your answer
Step-by-step explanation:
Answer:
f(x + h) = 3x³ + x² + 9h²x + 3h³ + h² + 9hx² + 2hx
General Formulas and Concepts:
- Order of Operations: BPEMDAS
- Distributive Property
- Expand by FOIL (First Outside Inside Last)
- Combining like terms
Step-by-step explanation:
<u>Step 1: Define function</u>
f(x) = x² + 3x³
f(x + h) is x = x + h
<u>Step 2: Simplify</u>
- Substitute: f(x + h) = (x + h)² + 3(x + h)³
- Expand by FOILing: f(x + h) = (x² + 2hx + h²) + 3(x + h)³
- Rewrite: f(x + h) = (x² + 2hx + h²) + 3(x + h)²(x + h)
- Expand by FOILing: f(x + h) = (x²+2hx+h²) + 3(x² + 2hx + h²)(x+h)
- Distribute/Expand: f(x + h) = (x²+2hx+h²) + 3(x³+3hx²+3h²x+h³)
- Distribute 3: f(x + h) = (x²+2hx+h²)+(3x³+9hx²+9h²x+3h³)
- Combine like terms: f(x + h) = 3x³+x²+9h²x+3h³+h²+9hx²+2hx
Answer:
I know for a fact that x is 4.3 so that means 4.2 is less than x and 4.4 is greater than x
here are the steps whether you like it or not
step:1 4.1^2+1.3^2=18.5
step:2 √18.5=4.3